ACTIVATION OF COGNITIVE ACTIVITY OF STUDENTS MEANS OF IMITATION-GAME LEARNING - O.V. Kovshar (Academy of Cognitive and Natural Sciences, 2004)
In the article the author defermines the role of imitative and educafion with playind in activisation of studyind pupils' activity at classes, dives the examples of pedagogical dames and describes one of them - brain storm.